2014
DOI: 10.1080/21693277.2014.881728
|View full text |Cite
|
Sign up to set email alerts
|

A review of turning of hard steels used in bearing and automotive applications

Abstract: Hard turning is a recent technology that involves machining of hard steels using modern machine tools. Hard machining presents challenges in terms of selection of tool insert with improved tool life and high-precision machining. Turning of hardened steels using single-point cutting tool has got considerable interest among manufacturers of ball bearings, automotive, gear, and die industry. Hard turning in the automotive industry and bearing applications typically has a number of potential benefits over traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 58 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…Power consumed in materials machining is mainly converted into cutting heat, which directly or indirectly causes machining problems, such as tool wear and a loss of machining precision [16]. An experimental study of diamond milling of silicon carbide was designed by Iqbal et al [17]; they found that cutting temperature decreases with an increase in cutting depth at a higher feed rate, but increases at low feed rates.…”
Section: Introductionmentioning
confidence: 99%
“…Power consumed in materials machining is mainly converted into cutting heat, which directly or indirectly causes machining problems, such as tool wear and a loss of machining precision [16]. An experimental study of diamond milling of silicon carbide was designed by Iqbal et al [17]; they found that cutting temperature decreases with an increase in cutting depth at a higher feed rate, but increases at low feed rates.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are preferred for their exceptional mechanical properties like high hardness; high wear opposition. These materials are extensively used in applications like chain sprocket, steel ball bearings, transmission shaft, valve casing, engine parts, gears, bearing, dies, punches, nozzles, railways components, helicopter camshaft [1][2]. The conventional processes for turning hardened steel are electricdischarge and grinding; and are in limited is use due to high tooling cost, low surface finish and material removal rate, faster wear.…”
Section: Introductionmentioning
confidence: 99%
“…Turning of high hardness material with hardness range 45-70 HRC is carried out by a single point cutting tool and is referred to as hard turning. It is widely used in aviation, automotive industries for manufacturing components such as shafts, bearings, camshaft gears and landing gear, engine attachment fittings and constant velocity joints, and so on [1]. The hardened steels are favored because of their special mechanical properties like high hardness, high wear opposition etc.…”
Section: Introductionmentioning
confidence: 99%